A desobediência civil tributária como uma possibilidade de realização dos direitos fundamentais - Renato Toledo da Cunha (2021)
The present work aims to evaluate the tax civil disobedience as a possibility of achieving the ethical purposes of the Democratic Constitutional State, in which a fair order is the one that declares fundamental rights with priority and thus defines the idea of justice. In other words, a State in which fundamental rights represent the content of material justice, the core of the political obligation. It is in such context that lies the theoretical possibility of exercising indirect tax civil disobedience, which immediately aims a positive tax law, with the mediate purpose of obtaining changes or adjustments to public policies through the financial law, regarding the allocation of tax revenues in order to achieve the concrete realization and guarantee of the ethical universality of a Democratic Constitutional State that moves away from or confronts itself with the sustaining and indispensable ends of the democratic unity itself. The contemporary constitutional interpretation must consider a broad framework of values, explicit and implicit in the constitutional system itself, as a logical-philosophical consequence of its unity, always open to pluralist and antagonistic positions in the social framework. Civil disobedient conduct – in which the term civil is understood as a synonym for respect for the political-historical obligation – requires, for the affirmation of its existence, the definition of limits and conditions in the legal-political context in which it is established. In summary, from a methodological stand point, we seek to carry out a historical, systematic and critic reflection on the fair and ethical within the Democratic Constitutional State to conclude, in the end, that the tax civil disobedience presents itself as a form of participation by the collective of citizens, based on the very principles that inform constitutional legitimacy, in the construction, opening and defense of the democratic constitution. In a participatory and solidary citizenship, tax civil disobedience is part of a complex political and legal process of interpretation of the constitution and, ultimately, of the ethical role of the Democratic Constitutional State.